Outcome of Root Canal Treatment of Necrotic Teeth with Apical Periodontitis Filled with a Bioceramic-Based Sealer - Kawther Bel Haj Salah; Sabra Jaâfoura; Mahdi tlili; Marwa Ben Ameur; Saida Sahtout (International Journal of Dentistry, 2021)
Introduction. Apical periodontitis is among the most common pathologies in endodontics. The treatment of apical periodontitis has always been an important occupation in the modern practice of endodontics, and the failure has been associated with nonhermetic root canal filling. With that in mind, bioceramic-based sealers have been incorporated into endodontic practice. The purpose of this study was to evaluate the outcome of nonsurgical root canal treatment (RCT), using a single-cone and Bioroot RCS filling of necrotic teeth with apical periodontitis. Materials and Methods. This follow-up study included patients treated in the department of Restorative Dentistry and Endodontics in the Dental Clinic of Monastir, from January 2018 to December 2019. The study intended to include all adult patients presenting a symptomatic or asymptomatic apical periodontitis. Once the diagnosis was performed, the patients were divided into two groups: a one-session treatment group and a two-session treatment group. All cases were obtured with BioRoot using a single-cone technique with a minimum of a 6-month recall. At 6-month follow-ups, teeth were classified as healed, healing (success), or not healed (failure), based on clinical and radiographic findings. Results. Twelve patients met the inclusion criteria, six patients per group. Seven patients returned for follow-ups. At 6-month follow-ups, the overall success rate was 100%, with 57.1% determined to be “healed” and 42.8% determined to be “healing.” All the PAI scores decreased compared to the baseline situation. Conclusion. The results obtained showed the contribution of BioRoot RCS in the healing of periapical lesions. Accordingly, bioceramic-based sealers seem to optimize the prognosis of root canal treatments.